Hubungan antara Tipologi Strategi Kompetitif, Kematangan Teknologi Informasi, dan Ukuran Perusahaan Perbankan dengan Respon Strategik dalam Menghadapi Globalisasi - Johan Arifin (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2002)
The globalization of competition has caused many banking firms in the financial service industry to integrate their information systems. Based on a selective review of literature in strategic and information management disciplines, this research is developed to study the banking firms' strategic response in order to face APEC Free Trade Agreements. This study describes the relationship between competitive strategy typology, information technology maturity, and firms’ size with firms' strategic response to APEC Free Trade Agreements. The firms' strategic response is reflected by the firms' willingness to increase the information technology investment.According to a survey of 66 banking firms in the financial service industry, competitive strategy typology does not have relationship with the banking firms' willingness to increase the information technology investment. Nevertheless, this study shows that information technology maturity and firms' size have relationship with the banking firms' willingness in order to increase the information technology investment. Key words: Globalization, APEC, strategic response, and competitive strategy typology, information technology maturity, firms’ size.